(untitled) (Journal of the College of Basic Education, 2023)
Religion is an important factor in building society, and religion is considered one of the ethnographic components.The state and religion are also among the important human phenomena that determine the behavior of human societies.Because it aims to guide people and their cultural and social elevation, and its impact is clearly reflectedin the political map of the world.In the modern era, despite the spread of national awareness and the predominance ofthe economic and political factors over the religion factor. Religion still plays a role in sparking conflicts.among peoples, especially primitive ones, and in some developing countries and even in some countries of the worldOther examples include the differences between Catholics and Protestants in the United Kingdom.Kashmir is considered temporary and liable to explode due to the religious factor between India and Pakistan.Whereas political geography focuses in its study on the political unit (the state)It studies religion as one of the elements that contribute to the strength or weakness of the state.Weak factor due to the multiplicity of religious sects within the country or the region.Religion within the political unit is sometimes a threatening factor to the national security of that political unit.Because of the religious differences between those sects and sometimes a factor of strength as a result of maturity in understandingReligion and jurisprudence.